Implementasi Kebijakan Pemberian Bantuan Sosial Masyarakat Miskin yang Terdampak Covid-19 di Kecamatan Bangil Kabupaten Pasuruan Jawa Timur - Mifta Farid; Willy Trihardianto; Asih Widi Lestari (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
This study examines the implementation of the policy of providing social assistance to the poor affected by COVID-19 in Bangil sub-district, Pasuruan district, East Java. The purpose of the research is to understand how the process of formulating policies for providing social assistance to poor families during the pandemic, implementing social assistance policies and the impact seen after aid is distributed. This research was conducted in Bangil sub-district, Pasuruan district, East Java. The method used is qualitative. Data collection techniques through interviews, observations and documentation. Data analysis is done by selecting, simplifying, classifying, presenting and drawing conclusions. Social assistance is prone to irregularities because it is closely related to budgeting, implementation, accountability and there is no clear limit on the expenditure of funds. The application for social assistance must have a proposal, while poor families cannot make proposals. Data on poor families is not accurate, the distribution of prosperous rice (Rastra) is not well targeted, poor families cannot make proposals and do not receive full assistance. Cross sectoral collaboration is needed to help poor families improve their social and economic lives. Bangil sub district empowers poor families by providing assistance in the form of joint business groups.